2003
DOI: 10.1016/s0741-5214(03)01042-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of abdominal aortic endovascular prostheses in France from 1999 to 2001

Abstract: This study shows the need for improvement in the clinical evaluation of new devices and medical technologies in France. Study findings also confirm the significant incidence of adverse outcomes and necessity for routine surveillance after EVR of AAA with AEP. However, risk/benefit analysis is difficult because most procedures were not carried out within a proper investigational context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…These promising reports of early endovascular success were counterbalanced by the concomitant reports of late failures, such as endoleak, migration, rupture, stent fracture, secondary procedure, and the high cost of required laparoscopic equipment. [3][4][5] We believe that the gold standard for an AAA is endoaneurysmorrhaphy (EA) with intraluminal graft placement as described by Creech,6 because EA has a lower degree of reintervention in comparison to an endovascular aneurysm repair regarding the long-term results. To decrease the incidence of complications and improve the postoperative course, Matsumoto et al 7 developed a surgical technique for AAA repair using a mini-laparotomy that allows anastomoses to be carried out even at the external iliac level via a limited abdominal incision.…”
Section: Introductionmentioning
confidence: 99%
“…These promising reports of early endovascular success were counterbalanced by the concomitant reports of late failures, such as endoleak, migration, rupture, stent fracture, secondary procedure, and the high cost of required laparoscopic equipment. [3][4][5] We believe that the gold standard for an AAA is endoaneurysmorrhaphy (EA) with intraluminal graft placement as described by Creech,6 because EA has a lower degree of reintervention in comparison to an endovascular aneurysm repair regarding the long-term results. To decrease the incidence of complications and improve the postoperative course, Matsumoto et al 7 developed a surgical technique for AAA repair using a mini-laparotomy that allows anastomoses to be carried out even at the external iliac level via a limited abdominal incision.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that almost half of the EVARs were coded as open repairs, which is likely due to both the novelty of the intervention and an entirely new code for EVAR being introduced in April 2002. Our data suggest that studies using the traditional method to identify open AAA repair or EVARs in administrative database [2,5–12] (i.e. combination of a diagnosis for AAA with a procedure code for repair) will both miss and misclassify many procedures.…”
Section: Discussionmentioning
confidence: 95%
“…We determined whether the cases of open and EVAR AAA repair identified from our surgical scheduling system had an ICD‐10‐CA code for non‐ruptured AAA and the CCI code for AAA procedure by either EVAR or open repair (). This coding algorithm (using a combination of diagnostic and procedural codes) was used in all previously published studies that used administrative databases to examine AAA repair [2,5–12]. The diagnostic code for non‐ruptured AAA did not have to be a primary (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations